Pemberdayaan Masyarakat Desa Rambu Kongga melalui Pemanfaatan Rebusan Daun Sirsak untuk Pengendalian Hipertensi (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Hypertension is one of the most common health problems in the community and often triggers serious complications, but there are still many people who do not understand how to manage hypertension naturally and sustainably. The purpose of this activity is to increase the awareness and knowledge of Rambu Kongga Village residents about the prevention and control of hypertension through an educational approach and the use of local herbal ingredients, namely soursop leaves. This activity included health checks, health counseling on hypertension, and training on making soursop leaf cooking water. A total of 22 participants were involved in this activity and from the initial examination results it was found that 8 people had hypertension. Therefore, the intervention was carried out by giving soursop leaf cooking water for 3 days and the results showed that all participants who underwent the intervention experienced a significant decrease in blood pressure. In addition, the enthusiasm of the residents in participating in this activity was also quite high. These results show that the combination of health education and utilization of local herbal plants can be an effective community empowerment strategy in helping to control hypertension naturally and easily applied in the daily environment.